MAJAPAHIT SEBAGAI SIMBOL KEKUASAAN: PENGARUHNYA TERHADAP VISI POLITIK DI INDONESIA - Al Ghiffari, Ahda Abid; Mulyatari, Dwi; Pradjoko, Didik (UI Scholars Hub, 2025)
This article examines the image of Majapahit as a symbol of power and political construction in Indonesia in the early 20th century AD until the 1960s. Majapahit is known in the imagined of past greatness. Its image was then accepted in the context of nationalism, revolutionary ideology, and the struggle against colonialism. Over its development, the symbols and constructions of the image of Majapahit shaped its influence in the political vision of nationalists in Indonesia. Entering the era of Indonesian Independence, the debate about Majapahit had formed an elements in the national political vision. This article aims to understand the construction and transformation of Majapahit symbolism in the history of Indonesian nationalist thought. This article uses historical research methods, namely topic selection, heuristics (source collection), verification (source criticism), interpretation, and historiography. The sources used are based on published speech manuscripts, historiographical works, writings in contemporary nationalist newspapers, correspondence letters, and relevant secondary sources. This article finds that Majapahit as a symbol and construction faced its own challenges. The diversity of the spectrum of nationalism in Indonesia, particularly the element of Islamic nationalism, challenged the construction of Indonesia’s past in the Majapahit symbolism from the beginning of the 20th century AD until the 1960s. This multispectrum of Indonesian nationalism ultimately became one of the reasons why the Majapahit symbolism was unacceptable as a modern political identity and vision.